أنماط الجملة ودلالاتها في ديوان أبي بكر الصديق - حرزولي, العزوزي; حامدي, عفاف; اللبي, يسمينة (University of Eloued جامعة الوادي, 2024)
يعد الشعر العربي وعاءً لغوياً وفنياً تجسدت فيه جمالية اللغة العربية، وقد تنوعت مظاهر هذا الابداع الشعري وتعددت أشكاله، ومن ضمن هذه الابداعات الشعرية البارزة: ديوان أبي بكر الصديق رضي الله عنه. ومن هذا المنطلق تأتي هذه المذكرة لتسلط الضوء على أنماط الجملة ودلالتها في ديوان أبي بكر الصديق، ومنه طرحنا الإشكال التالي: ما هي أنماط الجملة السائدة في ديوان أبي بكر الصديق بما يمثله من مزايا مكانية وزمانية تعينه للدراسة؟ وعليه فقد تضمنت هذه الدراسة جانب نظري وجانب تطبيقي، تناولنا في الجانب النظري تعريف الجملة وأقسامها ودلالاتها، أما الجانب التطبيقي تتبعنا فيه بنية الجملة سواءً كانت فعلية أم اسمية ملتزمين بإظهار معنى الأبيات. وقد خلصنا إلى: 1- ديوان أبي بكر الصديق تراث لغوي جدير بالدراسة والتحليل. 2- اختلاف النحاة القدامى والمحدثين في تحديد تعريف الجملة، فمنهم من اقتصر على عنصر الإسناد ومنهم من اقتصر على عنصر الإفادة. 3- تغلب الجمل الفعلية على الجمل الاسمية في الديوان. 4- استعمل الخليفة في ديوانه أسلوب التوكيد للدلالة على أن الكلام الذي يقوله الخليفة ليس فيه تَجَوُّز ولا حذف ويفيد تقوية المؤكد وتمكينه في ذهن السامع وقلبه. ومن خلال ما سبق نوصي الباحثين في الدراسات اللغوية أن يولوا اهتماما بدراسة ديوان أبي بكر الصديق رضي الله عنه الذي يُعد ثروة لغوية وأن يكملوا ما تبقى من جوانب الدراسة. Poetry serves as a linguistic and artistic vessel that embodies the beauty of the Arabic language. The manifestations of this poetic creativity are diverse and multifaceted. Among these prominent poetic works is the anthology of Abu Bakr al-Siddiq, may Allah be pleased with him. This thesis aims to shed light on the sentence patterns and their meanings in the anthology of Abu Bakr al-Siddiq. Consequently, we posed the following research question: What are the prevailing sentence patterns in the anthology of Abu Bakr al-Siddiq, considering its spatiotemporal advantages for study? This study comprises both theoretical and practical aspects. In the theoretical part, we dealt with the definition of the sentence, its types, and its meanings. In the practical part, we analyzed the sentence structure, whether nominal or verbal, adhering to the elucidation of the verses' meanings. Our findings are as follows: 1. The anthology of Abu Bakr al-Siddiq is a linguistic heritage worthy of study and analysis. 2. There is a discrepancy among ancient and modern scholars in defining the sentence. Some limited it to the element of predication, while others confined it to the element of benefit. 3. Verbal sentences dominate over nominal sentences in the anthology. 4. The Caliph employed the method of emphasis in his anthology to indicate that his speech is free from exaggeration and omission, thereby strengthening the confirmed statement in the listener's mind and heart. Based on the above, we recommend that researchers in linguistic studies pay attention to the anthology of Abu Bakr al-Siddiq, which is considered a linguistic treasure, and continue to explore the remaining aspects of this study.
لسانيات عامة
Keywords: Abu Bakr Al-Siddiq; sentence semantics; sentence patterns.; أبو بكر الصديق، دلالات الجملة، أنماط الجملة.